The Effect of Discovery Learning Model Assisted by E-Module on Students’ Physics Learning Outcomes - Aprilia Dewi Artika; Joni Rokhmat; I Wayan Gunada (International Journal of Contextual Science Education, 2026)
This study aimed to determine the effect of the Discovery Learning model assisted by e-modules on students’ physics learning outcomes. This study employed a quasi-experimental design with a nonequivalent control group design. The population consisted of all students of class XI A at SMAN 1 Kediri in the 2025/2026 academic year. Saturated sampling was used, with class XI A2 as the experimental class consisting of 20 students and class XI A1 as the control class consisting of 21 students. The research instrument was a multiple-choice test consisting of 25 items that had been tested for validity, reliability, item difficulty level, and discrimination index. Data analysis techniques included normality testing, homogeneity testing, and hypothesis testing using the t-test. The results showed that the implementation of the Discovery Learning model assisted by e-modules significantly affected students’ physics learning outcomes. This learning model increased students’ engagement in the learning process and encouraged them to actively discover concepts independently. These findings indicate that Discovery Learning assisted by e-modules not only improves students' physics learning outcomes but also promotes active engagement, independent learning, and conceptual understanding in digital learning environments.